Justice in the States of South America: Commutative Justice and Distributive Justice - Dueñas Roque, Diana Milagros (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The problem lies in the vagueness of the type of justice adopted in the Political Constitutions of South America; such absence generates that the justice system and social equality are implemented inadequately. The purpose is to propose the application of commutative justice in the administration of justice and distributive justice in equality. The methodology used is the quantitative approach, transactional, descriptive design. The results present disagreement and distrust in the justice system and that the lack of precision of the type of justice generates an increase in social inequality and an economic crisis.